The dust-continuum size of TNG50 galaxies at z = 1-5: a comparison with the distribution of stellar light, stars, dust, and H2 - Popping, Gergö; Pillepich, Annalisa; Calistro Rivera, Gabriela; Schulz, Sebastian; Hernquist, Lars; Kaasinen, Melanie; Marinacci, Federico; Nelson, Dylan; Vogelsberger, Mark (Monthly notices of the Royal Astronomical Society, 2022)
We present predictions for the extent of the dust-continuum emission of main-sequence galaxies drawn from the TNG50 simulation in the range z = 1-5. We couple the radiative transfer code SKIRT to the output of the TNG50 simulation and measure the dust-continuum half-light radius of the modelled galaxies, assuming a Milky Way dust type and a metallicity-dependent dust-to-metal ratio. The dust-continuum half-light radius at observed-frame 850 $\m is up to ∼75 per cent larger than the stellar half-mass radius, but significantly more compact than the observed-frame 1.6 $\m (roughly corresponding to H band) half-light radius, particularly towards high redshifts: the compactness compared to the 1.6 $\m emission increases with redshift. This is driven by obscuration of stellar light from the galaxy centres, which increases the apparent extent of 1.6 $\m disc sizes relative to that at 850 $μ$m. The difference in relative extents increases with redshift because the observed-frame 1.6 $\m emission stems from ever shorter wavelength stellar emission. These results suggest that the compact dust-continuum emission observed in z > 1 galaxies is not (necessarily) evidence of the build-up of a dense central stellar component. We find that the dust-continuum half-light radius closely follows the radius containing half the star formation and half the dust mass in galaxies and is ∼80 per cent of the radius containing half the H2 mass. The presented results are a common feature of main-sequence galaxies.
Advance access publication 2021 November 18
Gesehen am 21.04.2022